Maternity perception by pregnant women living with HIV - Thelma Spindola; Karla Temístocles de Brito Dantas; Natália Fernanda Vitipó Cadavez; Vinícius Rodrigues Fernandes da Fonte; Denize Cristina de Oliveira (Universidad de Antioquia, 2015)
Objective.Identify the perceptions of pregnant women living with HIV about motherhood and understand the expectations and feelings experienced by these women. Methodology. Study with descriptive design and qualitative approach, carried out with 10 pregnant women living with HIV who attend the prenatal service of a university hospital in Rio de Janeiro, Brazil. The participants answered a semi-structured interview. Data were analyzed using the content analysis technique. Results. Pregnant women in their descriptions revealed that motherhood gives them different perspectives on the present and future. They see it as a good thing, a responsibility to care for the child, and consider bearing a child to be a gift. Conclusion. For pregnant women living with HIV, motherhood is a positive experience in their lives. Nurses must be sensitive to the needs of this group and aware of their role in health care and preventing any possible complications that may affect the mother and her baby.